2017
DOI: 10.4236/wjcd.2017.712043
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Ambulatory Blood Pressure Monitoring to the Management of Arterial Hypertension at Blaise Compaoré University Hospital

Abstract: Background: Hypertension is a major public health concern in Burkina Faso. Its management relies on in-office medical setting blood pressure monitoring which is known to be an imperfect diagnosis tool. Objective: This study aims to assess the contribution of ambulatory blood pressure monitoring in the management of hypertension at Blaise Compaoré University Hospital. Methods: A monocentric descriptive retrospective study was conducted in the cardiology outpatient unit of Blaise Compaoré University Hospital. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
2
Order By: Relevance
“…In another study carried out in an Irish population, 31.7% of patients had a change in their medication, a figure which was lower than that reported in our study where 51.7% of patients had a change in medication prescribed. Also, we observed a higher proportion of patients who had adjustments made in their medications compared to 36.1% reported in a recent publication which included outpatients at a teaching hospital in Benin . Furthermore, a smaller proportion of patients discontinued all medications in our study compared to that reported by Kambiré et al The observed differences may be as a result of differences in population characteristics and thresholds for BP control in different settings.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In another study carried out in an Irish population, 31.7% of patients had a change in their medication, a figure which was lower than that reported in our study where 51.7% of patients had a change in medication prescribed. Also, we observed a higher proportion of patients who had adjustments made in their medications compared to 36.1% reported in a recent publication which included outpatients at a teaching hospital in Benin . Furthermore, a smaller proportion of patients discontinued all medications in our study compared to that reported by Kambiré et al The observed differences may be as a result of differences in population characteristics and thresholds for BP control in different settings.…”
Section: Discussioncontrasting
confidence: 70%
“…Also, we observed a higher proportion of patients who had adjustments made in their medications compared to 36.1% reported in a recent publication which included outpatients at a teaching hospital in Benin . Furthermore, a smaller proportion of patients discontinued all medications in our study compared to that reported by Kambiré et al The observed differences may be as a result of differences in population characteristics and thresholds for BP control in different settings. Additionally, we observed that majority of patients with WUCH were either maintained on previously prescribed treatment or therapy deintensified when the clinician interpreted the ABPM report.…”
Section: Discussioncontrasting
confidence: 70%